Description of Writing Exposition Text Using the Discovery Learning Model Assisted with Media Canva - Iis Siti Salamah Azzahra; Yunisya Zyan Azhari (JLER (Journal of Language Education Research), 2024)
This study explains the results of students' writing in writing exposition texts. The learning outcomes of these students were divided into two tests as consideration for using the discovery learning model using Canva media, in the first test students carried out learning without using the learning model using Canva media while in the second test students carried out learning using the discovery learning model using Canva media. . This study uses a qualitative descriptive method to show the value of students before and after using the discovery learning model using Canva media. The role of Canva media in learning to write exposition texts is to guide and provoke students to better understand material and use digital media to make learning easier and more efficient. The subjects in this study were 15 class VIII A students at SMP Negeri 3 Cimahi. Acquisition of scores analyzed include the total score of students, the average score of students, analysis of the lowest, middle and highest scores. This study shows the effectiveness of learning to write exposition texts using the discovery learning model using Canva media by obtaining a fairly good average score of 78.5 analysis of lowest, middle and highest scores. This study shows the effectiveness of learning to write exposition texts using the discovery learning model using Canva media by obtaining a fairly good average score of 78.5 analysis of lowest, middle and highest scores. This study shows the effectiveness of learning to write exposition texts using the discovery learning model using Canva media by obtaining a fairly good average score of 78.5.